Serum Concentrations of Imidazole Dipeptides and Serum Amyloid A in a Bottlenose Dolphin (Tursiops truncatus) with Rhabdomyolysis: Potential Biomarkers for Muscular Damage - Nanami Arakawa; Mika Otsuka; Takahisa Hamano; Momochika Kumagai; Sanae Kato; Takuya Hirai; Akira Yabuki; Osamu Yamato (Animals, 2025)
Imidazole dipeptides (IDPs), including anserine, carnosine, and balenine, are predominantly found in the skeletal muscles of vertebrates. Balenine is the major IDP in cetaceans. Serum amyloid A (SAA) is an acute phase protein released in response to damage or injury in various tissues, including skeletal muscles. A captive bottlenose dolphin (Tursiops truncatus) died due to rhabdomyolysis and subsequent acute kidney injury that probably originated from accidental muscle trauma. In this study, concentrations of IDPs and SAA were measured using stored serum collected from the affected dolphin with intermittent continuous damage of skeletal muscles to demonstrate the pathological relevance of these parameters and their usefulness as biomarkers for muscle damage in dolphins. The IDP concentration was measured using the high-performance liquid chromatography-ultraviolet method. The SAA concentration was measured using an enzyme-linked immunosorbent assay (ELISA) specific to dolphin SAA and a latex turbidimetric immunoassay (LTI) specific to human SAA. Herein, the IDP concentration was altered similarly to serum muscular enzymes, including creatinine kinase (CK) and aspartate aminotransferase (AST). However, IDP concentrations were elevated one day earlier than CK and AST levels at disease onset. Furthermore, IDP concentrations were similarly altered when assessed using both ELISA- and LTI-SAAs, and the change in IDP concentration coincided with that in LTI-SAA based on the statistical analysis. These data suggest that IDP concentration could detect muscle damage and injury, including necrosis and inflammation, in dolphins.